2020
DOI: 10.1016/j.ebiom.2020.103040
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nivolumab and ipilimumab in patients with malignant pleural mesothelioma is related to a subtype of effector memory cytotoxic T cells: Translational evidence from two clinical trials

Abstract: Background: Combined immune checkpoint inhibitor (ICI) treatment targeting PD-1 and CTLA-4 was suggested to yield clinical benefit over chemotherapy in malignant pleural mesothelioma (MPM), whereas aPD-1 monotherapy failed to provide benefit in phase-III trials. Success of ICI depends on the presence and activation of tumor-specific T cells. Therefore, we investigated whether T-cell characteristics are underlying clinical efficacy of ICI treatment in MPM. Methods: Comprehensive immune cell profiling was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The INITIATE trial (Table 4 ) which had an estimated OS of approximately 12.7 months (Table 4 ) [ 72 74 ] along with the NivoMes trial (Table 3 ) were recently re-examined to complete a comprehensive immune cell profiling of samples [ 74 ], and the results demonstrated that the combination therapy induced a profound increase in the proliferation and activation of effector memory T cells which was not observed in the monotherapy, suggesting a clear benefit for the combination therapy, and therefore this observation warrants a larger Phase III trials of this combination therapy in the salvage setting.…”
Section: Immunotherapy In Mpm In the Historical Settingmentioning
confidence: 99%
“…The INITIATE trial (Table 4 ) which had an estimated OS of approximately 12.7 months (Table 4 ) [ 72 74 ] along with the NivoMes trial (Table 3 ) were recently re-examined to complete a comprehensive immune cell profiling of samples [ 74 ], and the results demonstrated that the combination therapy induced a profound increase in the proliferation and activation of effector memory T cells which was not observed in the monotherapy, suggesting a clear benefit for the combination therapy, and therefore this observation warrants a larger Phase III trials of this combination therapy in the salvage setting.…”
Section: Immunotherapy In Mpm In the Historical Settingmentioning
confidence: 99%
“…Nivolumab, an IgG4 mAb against PD-1, was approved following the pivotal trial CheckMate-037, on December 22, 2014, for the treatment of patients with unresectable of metastatic melanoma who have experienced disease progression following ipilimumab and, if BRAF V600 mutation-positive, a BRAF inhibitor. Between 2015 and 2020, new indications were approved for the treatment of patients with metastatic NSCLC with progression on or after platinum-based chemotherapy ( 49 , 50 ), for treatment in combination with ipilimumab or as a single agent for unresectable or metastatic melanoma patients ( 51 ), for the treatment of patients with advanced renal cell carcinoma ( 52 ), classical Hodgkin’s lymphoma ( 53 ), recurrent or metastatic squamous cell carcinoma of the head and neck (HNSCC) ( 54 ), locally advanced or metastatic urothelial carcinoma, hepatocellular carcinoma ( 55 ), metastatic SCLC ( 56 ), metastatic or recurrent NSCLC ( 57 ), esophageal squamous cell carcinoma (ESCC) ( 58 ), and for patients with unresectable malignant pleural mesothelioma ( 59 , 60 ).…”
Section: Fda-approved Anti-pd-1/pd-l1 Therapiesmentioning
confidence: 99%
“…The ability of T cells to produce effector molecules ex vivo is a measure of T cell effector function. Understanding the effector status of T cells is important as ICB induces activation and proliferation of circulating and intratumoral T cells which correlates with response ( 78 , 79 ). While MPE CD8 + T cells can produce IFN γ , granzyme B and perforin ex vivo , the frequency of MPE T cells that secrete these molecules is reduced compared to T cells from matched peripheral blood samples ( 67 , 70 ).…”
Section: Cellular Characteristics Of Malignant Pleural Effusions Without Icbmentioning
confidence: 99%